Communal coping and rumination in the aftermath of Chile earthquake: Multiple mediation analysis of the relationship between subjective severity and posttraumatic growth. (31st May 2018) - García, Felipe E.; Wlodarczyk, Anna
Abstract: Communal coping and collective participation were recently proposed as a potential mechanism that may favour not only individual's capacity to bounce back but also community cohesion and social well‐being and posttraumatic growth in the aftermath of natural disasters. To date, there is a lack of studies simultaneously assessing the effect of communal coping strategies and cognitive strategies on the development of posttraumatic growth. Therefore, the aim of this study was to examine the role of communal coping strategies and cognitive strategies such as intrusive and deliberated rumination as potential mediators between subjective severity of the event and posttraumatic growth and positive adjustment in the context of natural disaster. The questionnaire was administrated to 225 people affected by the most intense earthquake recorded in Chile in this century. The results of multiple mediation analysis showed that both cognitive strategies, such as deliberative rumination, and communal coping strategies, such as communal positive reappraisal and participation in spiritual rituals, are potential mediators between subjective severity and posttraumatic growth. Overall, the present work offers researchers and professionals interested in this area of study an interesting approach to analyse individual and collective coping strategies and its interrelation.